AB0648 COMPARING SYMPTOMS, TREATMENT PATTERNS, AND QUALITY OF LIFE OF ANKYLOSING SPONDYLITIS PATIENTS AND NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS IN JAPAN. (2nd June 2020) - Tomita, T.; Aranishi, T.; Hagimori, K.; Nakajo, K.; Booth, N.; Holdsworth, E.; Hunter, T.
Abstract : Background: Axial spondyloarthritis (axSpA) is a chronic inflammatory disease of the axial skeleton associated with impaired health-related quality of life (QoL) and disability. Objectives: To better understand the symptoms, clinical characteristics, treatment patterns, and quality of life (QoL), of non-radiographic axial spondyloarthritis (nr-axSpA) patients and how they compare to ankylosing spondylitis (AS) patients in Japan. Methods: Data from a cross-sectional survey conducted with physician (rheumatologists, orthopedic surgeon, and internal medicine) and their consulting patients in Japan were analyzed. Data were collected from Jun-Aug 2018 via physician-completed patient record forms and patient self-completed forms. Patients who had physician confirmed diagnoses of AS and nr-axSpA were eligible to participate. Demographics, disease status (improving, stable, unstable, deteriorating), symptoms, and medication use were reported by the physician, while work disability and QoL measures were reported by the patient using validated questionnaires. QoL and treatment patterns of nr-axSpA and AS patients were compared using parametric tests and non-parametric tests where appropriate. Results: Data from 41 physician, 72 AS patients, and 91 nr-axSpA patients were included in this analysis. A higher proportion of AS patients were male (70.8% vs. 58.2%; p=0.1040), yet this was not statistically significant. AS patients had a similar mean age (55.0 vs. 55.1; p=0.9762) compared to nr-axSpA patients. The majority of AS and nr-axSpA patients (61.1% vs. 62.9%; p=0.872) were not receiving a biologic. On average, AS and nr-axSpA patients reported similar rates of symptoms (Table 1 ). Patient reported outcomes such as the Assessment of SpondyloArthritis international Society Health Index (ASAS HI;6.0 vs. 6.4; p=0.6103), Patient Global Assessment (18.7 vs 22.7; p=0.4239), and the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI; 3.1 vs. 3.4; p=0.3453) were similar between AS and nr-axSpA patients. AS patients reported a lower EQ-5D VAS (62.6 vs. 71.3; p=0.0237) when compared to nr-axSpA patients. Conclusion: Nr-axSpA and AS being part of the same disease spectrum (i.e. axial spondyloarthritis) share the same clinical features. The burden of the disease, as assessed by QoL measurements, is also similar in AS and nr-axSpA patients. Disclosure of Interests: Tetsuya Tomita Consultant of: Eli Lilly and Company, Toshihiko Aranishi Employee of: Eli Lilly Japan, Kohei Hagimori Employee of: Eli Lilly Japan, Ko Nakajo Employee of: Eli Lilly Japan, Nicola Booth Consultant of: Janssen, Elizabeth Holdsworth Employee of: Adelphi Real World, Theresa Hunter Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company